2009 IEEE International Conference on Multimedia and Expo 2009
DOI: 10.1109/icme.2009.5202811
|View full text |Cite
|
Sign up to set email alerts
|

Understanding benford's law and its vulnerability in image forensics

Abstract: In this paper, we attempt to shed light on Benford's law from the viewpoint of probability theory and point out its limitation in image forensic applications. First, we consider a generalized form of Benford's law and relate it to a random variable of a certain probability density function such as the generalized Gaussian or Laplacian function. Then, we examine the application of the generalized Benford's law to image forensic applications and point out such an application is vulnerable to the histogram manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A similar assumption is adopted by many approaches aiming at detecting double JPEG compression. More precisely, some of the proposed works rely on detecting the violation of the so-called Benford's law (also known as FD law or significant digit law) [20]. Many fraud detection algorithms departs from the assumption that the analyzed data are well modeled by pre-defined stochastic models that present peculiar characteristics.…”
Section: B) the Fd Lawmentioning
confidence: 99%
“…A similar assumption is adopted by many approaches aiming at detecting double JPEG compression. More precisely, some of the proposed works rely on detecting the violation of the so-called Benford's law (also known as FD law or significant digit law) [20]. Many fraud detection algorithms departs from the assumption that the analyzed data are well modeled by pre-defined stochastic models that present peculiar characteristics.…”
Section: B) the Fd Lawmentioning
confidence: 99%
“…It is observed that many empirical data in the real world follow Benford's law such as stock market indices, tax returns and Fibonacci numbers (Wang, Cha, Cho, & JayKuo, 2009). Moreover, digital analysis (also first-digit law or Benford's Law) was discussed in the professional guidance on fraud detection in general (Debreceny & Gray, 2010).…”
Section: Formulas For Expected Digital Frequenciesmentioning
confidence: 99%
“…The morphing detector adopted in [5] is based on the hypothesis that unlike naturally generated data, manipulated data do not obey the Benford's law. Although high accuracy in detection of morphed random face images obtained using Benford's law, however, they note that using legitimate image processing techniques, one can create face images with similar Benford feature distribution [5,6].…”
Section: Introductionmentioning
confidence: 99%